Lost Of Family Reflected In Phillida Lloyd's The Iron Lady Movie (2011): An Individual Psychological Approach - Hanik, Ummy, Dr. Phil. Dewi Candraningrum, S.Pd.M.Ed, Titis Setyabudi, S.S.M.Hum (2013)
The major problem of this research is how manage the time for a career woman and her role as mother in The Iron Lady movie based on its structural elements and to analyze the movie based on individual psychological approach. The researcher applies a qualitative method.Qualitative study is a method which is used to analyze the effort to get the same right to be on the top reflected in Margaret, the object of the study in the movie. A result of the analysis shows the following conclusion: first, Margaret can proof to the world that women can be on the top with her effort to realize it, but in other side, she lost the warm and quality time for her nuclear family. In the method, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is The Iron Lady movie and the secondary data sources are books or any information which support the researcher in analyzing this research. Techniques of the collection data of the study is library research. The technique of the analysis data is descriptive analysis.